MODERN YOUTH SLANG: ITS SOURCES AND VARIETIES - Sheralieva Mukhlisa (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Any language develops through linguistic borrowings, regardless of how closed the country and society are. The process of language borrowings is also characteristic of the Russian language. This process is most active among young people. The author notes that the source of most borrowings in Russian youth slang are English, Korean and Japanese. This is due to the great interest of Russian youth in learning English and the culture of Korea and Japan. There are much fewer borrowings from other languages. This is due, among other things, to weak social ties with other states, and the significant difference between their cultures and the Russian one